New urban tourism in the Global South: The case of inner-city Johannesburg - Christian M. ROGERSON; Mitchell C.N. MALOVHA; Jayne M. ROGERSON (GeoSport for Society)
The phenomenon of ‘new urban tourism’ is attracting growing scholarly attention. In many cities a strong trend is for visitors increasingly to leave the confines of tourist precincts or zones and instead to venture into new city spaces. This tendency has been linked to the growth of ‘off-the-beaten track’ tours in many urban destinations in the Global North. The aim in this paper is to explore the development of ‘new urban tourism’ in one leading tourism city in the Global South. Johannesburg inner-city is the geographical focus of the study. Using interviews with tour operators as well as tourists, the analysis charts the evolution and major features of off-the-beaten track tours in inner-city Johannesburg from their beginnings in the 2010s decade. Arguably, new urban tourists in Johannesburg are experiencing ‘edgy tourism’ as they explore spaces of an inner-city which, in recent years, has a tarnished reputation as no-go zone because of its physical decline as well as crime and grime.